Radiologic and Neuropathologic Findings in Patients in a Family with Dentatorubral-Pallidoluysian Atrophy - Sunami, Y.; Koide, R.; Arai, N.; Yamada, M.; Mizutani, T.; Oyanagi, K. (American Journal of Neuroradiology, 2011)
SUMMARY: We describe the cases of 2 patients, a father and his son, with DRPLA who underwent MR examinations prior to death and in whom postmortem examinations of the brain were obtained. MR imaging findings had the following features: 1) atrophy of the cerebellum and brain stem were the common findings, 2) high-signal-intensity lesions in the cerebral white matter and brain stem were observed on T2-weighted images in the patient with adult-onset DRPLA, 3) signal-intensity changes in the cerebral white matter were restricted to the periventricular white matter in the patient with juvenile-onset DRPLA, but these changes appear in the advanced stage, and 4) progressive cerebral atrophy was more marked in the patient with juvenile-onset DRPLA. In the patients with DRPLA, the abnormal high signal intensity of the cerebral white matter or brain stem on MR images reflect the loss of myelinated fibers. Cerebral atrophy mainly reflects atrophy of the neuropile. ABCavidin-biotin-peroxidase complexDRPLAdentatorubral-pallidoluysian atrophyKBKlüver-Barrera